2020
DOI: 10.52845/cmi/2020v1i1a5
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Nurses’ Work in Psychiatric Clinic

Abstract: Purpose: This study aims to determine the siege and related factors of nurses working in psychiatric clinics. Method: This study was conducted as a related description design. The sample of the study consisted of 204 nurses working in psychiatric clinics. The data was collected using questionnaires generated by researchers from literature and workplace psychological abuse scales. Descriptive statistics (frequency and percentage) and chi-square independence test are used to determine whether there is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…With p<0.0001, the postdialysis serum creatinine concentration was significantly lower than the pre-dialysis group. Creatinine is almost entirely formed in the muscle, creatinine excretion is affected by muscle mass; thus, urinary excretion is the most accurate index to identify muscle mass [12][13]. Our Present study the serum cystatin C concentration were significantly increase in the after hemodialysis patient as compared to before hemodialysis (P < 0.0001).…”
Section: Discussionmentioning
confidence: 44%
“…With p<0.0001, the postdialysis serum creatinine concentration was significantly lower than the pre-dialysis group. Creatinine is almost entirely formed in the muscle, creatinine excretion is affected by muscle mass; thus, urinary excretion is the most accurate index to identify muscle mass [12][13]. Our Present study the serum cystatin C concentration were significantly increase in the after hemodialysis patient as compared to before hemodialysis (P < 0.0001).…”
Section: Discussionmentioning
confidence: 44%
“…Few of the related studies on hypertension from modern medicine were reviewed [19][20][21]. Studies on Ghrelin use in heart failure [22] and effectiveness of Yoga [23] were reported. Vata is disturbed with gati and ghandan functions of the body.…”
Section: Resultsmentioning
confidence: 99%
“…The aerobic and yoga activities effectively worked on hepatic steatosis and cardiovascular risks. The type of action should be selected upon the disease scenario of comorbidities, clinical findings, patients' comfort, and physical fitness for longterm maintenance as an adjunct therapy in case of NAFLD [20][21][22][23].…”
Section: Interventionmentioning
confidence: 99%